Suffragists in an imperial age U.S. expansion and the woman question, 1870-1929 - Sneider, Allison L. (Oxford University Press, 2008)
Allison Sneider tracks how debates over woman suffrage were framed and reframed in the context of national discussions of citizenship and voting rights for potential new citizens, both within U.S. borders and in the island territories in the Caribbean and the Pacific, from roughly 1870 to 1900.